The Improvement of Mathematical Communication Ability Using Problem-Based Learning Model on Junior High School Students - Fitri, Siti Aisah Nur; Pertiwi, Citra Megiana (IKIP Siliwangi, 2024)
Students' understanding of linear equations with one variable is still low. Of the total number of students in the class, namely 32 students, only 10 students scored above the minimum completeness criteria (KKM) while the remaining 22 scored below the KKM. This research aims to determine the improvement of mathematical communication skills by using problem-based learning better than ordinary learning. Two classes, an experimental group, and a control group, were selected for this study. The researchers tested the technique because experimental research requires both groups to have the same skill level. The researcher used a test of students' mathematical communication skills as a research tool in this study. The average N-gain score for students who apply the problem-based learning model with regular learning is 0.71 (high category), higher than students who receive regular learning. of 0.10 (low category). Then the N-gain score normality test was carried out, the results obtained were 0.023 in the experimental class and 0.216 in the control class and the results obtained were not normally distributed. Then proceed with non-parametric tests, from the results of the Mann-Whitney U-Test obtained by Asymp. Sig (1-tailed) is 0.000 ˂ which indicates it is rejected, meaning that the increase in mathematical communication skills of experimental class students is significantly better than that of the control class. The PBL model improves students' mathematical communication by promoting critical thinking, collaborative work, and active problem-solving. It also allows students to understand the practical relevance of mathematical concepts in real-life situations.